SURFACE POTENTIAL BEHAVIOR IN ISFET BASED BIO-(CHEMICAL) SENSOR - A. V. Surmalyan
The developments of ion-selective field-effect transistors (ISFET) are very furious and create pride. The importance of work in this field issued in last years because of increased ISFETs applications. Among these devices, proton-sensitive ISFETs are the more deeply analyzed. ISFET have a very fast response time, high sensitivity, small size, robustness and the potential for on-chip circuit integration.
Keywords: Physics; Instruments, apparatus, components common to several branches of physics